Secreted PGK1 and IGFBP2 contribute to the bystander effect of miR-10b gene editing in glioma - Yanhong Zhang; Rosalia Rabinovsky; Zhiyun Wei; Rachid El Fatimy; Evgeny Deforzh; Bai Luan; Leonid Peshkin; Erik J. Uhlmann; Anna M. Krichevsky (Elsevier, 2023)
MicroRNA-10b (miR-10b) is an essential glioma driver and one of the top candidates for targeted therapies for glioblastoma and other cancers. This unique miRNA controls glioma cell cycle and viability via an array of established conventional and unconventional mechanisms. Previously reported CRISPR-Cas9-mediated miR-10b gene editing of glioma cells in vitro and established orthotopic glioblastoma in mouse models demonstrated the efficacy of this approach and its promise for therapy development. However, therapeutic gene editing in patients' brain tumors may be hampered, among other factors, by the imperfect delivery and distribution of targeting vectors. Here, we demonstrate that miR-10b gene editing in glioma cells triggers a potent bystander effect that leads to the selective cell death of the unedited glioma cells without affecting the normal neuroglial cells. The effect is mediated by the secreted miR-10b targets phosphoglycerate kinase 1 (PGK1) and insulin-like growth factor binding protein 2 (IGFBP2) that block cell-cycle progression and induce glioma cell death. These findings further support the feasibility of therapeutic miR-10b editing without the need to target every cell of the tumor.